2009
DOI: 10.1038/ejcn.2009.18
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation does not affect serum lipids and lipoproteins in Pakistani immigrants

Abstract: Potential long-term negative effects of increased vitamin D consumption are not thoroughly examined. The aim of this study was to investigate possible negative effects of vitamin D supplementation on serum lipids and lipoproteins. A 1-year long randomised double-blinded placebo-controlled intervention study with two doses of vitamin D3 (10 and 20 mg/day) was carried out among 89 women (18-53 years of age) and 84 men (18-64 years of age) of Pakistani origin living in Denmark with low vitamin D status. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…We are not aware of any report previously examining the impact of vitamin D 3 supplementation on lipid profile and highly sensitive CRP in obese adolescents. Similar findings, however, have been reported in adults [22,23,26]. …”
Section: Discussionsupporting
confidence: 31%
“…We are not aware of any report previously examining the impact of vitamin D 3 supplementation on lipid profile and highly sensitive CRP in obese adolescents. Similar findings, however, have been reported in adults [22,23,26]. …”
Section: Discussionsupporting
confidence: 31%
“…So far only a few such intervention studies have been reported. Regarding serum TAG concentrations, which appear to be strongly associated with serum 25(OH)D, we have in our study of overweight and obese subjects found no effect on serum TAG of 20 000-40 000 IU vitamin D per week given for 1 year (Jorde et al, 2009);Heikkinen et al (1997) found no effect by supplementation with 300 IU vitamin D for 3 years in 323 postmenopausal women; Andersen et al (2009) found no change in 173 Pakistani subjects living in Denmark and given vitamin D in daily doses of 400 or 800 IU for 1 year; whereas Zittermann et al (2009) in their study on 200 overweight subjects found a significant 13% decrease in the serum TAG in those given 3320 IU daily for 1 year. These discrepancies could be due to the doses of vitamin D given as well as differences between the study groups.…”
Section: Vitamin D and Serum Lipidsmentioning
confidence: 76%
“…65 years) were given either 500 mg Ca and 17·5 mg cholecalciferol or a placebo, no effect on CRP or IL-6 concentration was observed over 3 years in either subjects with impaired fasting glucose or normal fasting glucose concentrations (87) . A short-term supplementation trial (12-week duration) with 1000 mg Ca and 20 mg cholecalciferol daily of postmenopausal women (n 39) had no effect on circulating concentrations of IL-6, TNF-a or CRP (161) . More recently, a large RCT on overweight and obese subjects (n 334) showed no effect of supplementation with Ca (500 mg/d) plus cholecalciferol (500 or 1000 mg/week) for 1 year on a wide range of cytokines and other inflammatory markers (193) .…”
Section: Inflammationmentioning
confidence: 99%